The Development of Augmented Reality And Its Implication for Vocational Education : A Literature Review - Patawari, A. Muzawwirah; Nurfauziah, Nurfauziah; Atmasani, Dian; Fadhilah, Nur Athiyyah (Jurusan Pendidikan Teknik Elektro, 2025)
This literature review explores the development of Augmented Reality (AR) technology and its implications for vocational education in the context of Industry 4.0. Drawing from 30 peer-reviewed sources published between 2020 and 2025, the study identifies four key thematic areas: the advancement of AR in industry, architecture and interior design, environmental awareness, and vocational education. The rapid growth of AR as a transformative technology has led to its widespread adoption across various sectors, offering improvements in visualization, training, human-machine interaction, and collaborative work environments. In vocational education, AR enhances student engagement, facilitates experiential learning, and supports skill development through immersive and interactive simulations. However, challenges persist, including infrastructure limitations, educators’ digital literacy, and a lack of contextualized research on AR's integration into vocational learning. This review highlights that while AR holds immense potential to modernize vocational education and meet industrial demands, its effective implementation requires strategic curriculum redesign, capacity building among educators, and stronger industry-education partnerships. The findings provide a theoretical foundation for developing adaptive vocational learning models aligned with digital transformation and future workforce needs.